Experimental Investigation of Steady and Unsteady Flow Field Upstream and Downstream of an Automotive Torque Converter Pump - B. V. Marathe; B. Lakshminarayana (International Journal of Rotating Machinery)
The objective of this investigation is to understand the steady and the unsteady flow field at the exit of an automotive torque converter pump with a view towards improving its performance. The measurements were conducted in a stationary frame of reference using a high frequency response five-hole probe and the data were processed to derive the flow properties in the relative (pump) frame of reference. The experimental data were processed at three different operating conditions: maximum efficiency point, design point and near-stall point. The unsteady values of flow properties (pressure, velocity and flow angles) were divided into five components: mean, periodic, blade aperiodic, revolution aperiodic and unresolved components.